2016
DOI: 10.15446/rsap.v18n3.44487
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of prevention for cervical cancer and breast cancer among medical students

Abstract: Objective To assess the knowledge, attitudes and practices of medical students for health promotion, primary prevention and early detection of breast neoplasm and uterine cervical neoplasm, as well as to make recommendations for improving the Public Health curriculum at the Universidad de los Andes. Methodology This study utilized a survey of medical knowledge, attitudes and practices applied to fifth year Colombian medical students attending the Universidad de los Andes in the first semester of 2013. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…After removing duplicates and, in compliance with the study protocol, a detailed screening of titles and abstracts of the manuscripts was made (Figure 1). The reporting of literature review on the KAP key question showed 55 studies using SPIDER and 11 using the PICO tool, divided per categories as follows: 50 among dentists [12,, eight among physicians [66][67][68][69][70][71][72][73], and eight between dentists and physicians [74][75][76][77][78][79][80][81].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing duplicates and, in compliance with the study protocol, a detailed screening of titles and abstracts of the manuscripts was made (Figure 1). The reporting of literature review on the KAP key question showed 55 studies using SPIDER and 11 using the PICO tool, divided per categories as follows: 50 among dentists [12,, eight among physicians [66][67][68][69][70][71][72][73], and eight between dentists and physicians [74][75][76][77][78][79][80][81].…”
Section: Resultsmentioning
confidence: 99%
“…The reporting of literature review on the KAP key question showed 55 studies using SPIDER and 11 using the PICO tool, divided per categories as follows: 50 among dentists [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], eight among physicians [ 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Por otra parte, según la Norma técnica colombiana sobre detección temprana de cáncer de mama, se recomienda implementar estrategias educativas con las mujeres mayores de 20 años para hacerse el autoexamen de mama; asimismo, a las mujeres que estén por encima de los 50 años de edad, de manera obligatoria, se les debe practicar una mamografía de cuatro proyecciones cada dos años, independientemente de la presencia o ausencia de signos o síntomas en la mama (9)…”
Section: Introductionunclassified